Антропоніми як продуктивний компонент ономастичного простору поезій Євгена Маланюка - Васейко, Юлія Святославівна; Vaseiko, Yuliia S. (Branch of Ukrainian Studies of Maria Curie-Sklodovska University in Lublin, 2016)
У статті проаналізовано ономастичний простір поезій відомого українського письменника Євгена Маланюка, основна увага зосереджена на власних назвах людей. Вивчено семантичне наповнення і функціональне навантаження антропонімів, прокласифіковано оніми за такими параметрами, як рід заняття / професійна діяльність (історичні постаті, діячі культури, літератури, науки), актуальність (сучасні авторові – історичні), походження (українські – зарубіжні), структура (ім’я – прізвище – ім’я та прізвище), детерміновано функції, котрі виконують власні назви людей, вжиті в заголовку й присвяті, описано роль антропонімів у формуванні концептуальності твору.

Onomastic space of the poetries of well-known Ukrainian writer Yeuhen Malaniuk is analyzed in the article, basic attention is concentrated on the personal names. The semantic meaning and functional srenhth of anthroponyms are studied, onyms are classified on the base of such parameters as: sort of employment / professional activity (persons that were active in historical, cultural, literary, scientific processes), actuality (modern authors towards historical authors), origin (Ukrainian – foreign), structure (name – surname – name and surname), there are determined functions of personal names that are used in title and dedication, there is described anthroponomies’ role in creating of conceptuality of the composition.
Anthroponyms as productive components in onomastic space of Yevhen Malanyuk’s poetries
Keywords: ономастичний простір; антропонім; ім’я; прізвище; заголовок; посвята; концепт; onomastic space; anthroponym; name; surname; title; dedication; concept; Yeuhen Malaniuk